PELAKSANAAN STANDAR KESETARAAN PELAYANAN MINIMAL ANGKUTAN UMUM MASSAL BERBASIS JALAN PADA BUS TRANS METRO PEKANBARU - Deni Prasetyo; Hendry Andry (UIR Press, 2019)
This study aims to determine the level minimum service equivalence standard on transbecous busses of pekanbaru, where the standard of equality is measured by 3 indicators : Accessibility, Service Priorities and Service Facilities. Type of research located in urban transport management UPTD Pekanbaru City Riau Provience is a survey description is priotize the list of questionnaires as a mean of data collection and data collected with this tool then used as the main raw material to assessing empirical conditions of the objectivity of existence research objektivities on location researched. There are 2 population groups and samples in this study15 the employee is people and society 20 people. Sampling technique used in the data collection is incidental sampling technique for employees and society. The types and techniques of data collection used consist of primary data, collected by questionnaire and interview : secondary data collected using observation techniques. While the data analysis technique used is using the frequency table tool. Based on this analysis technique the researchers assess and concluded that level the implementation of minimum service standar equality tranbecaus busses of Pekanbaru are at fairly prime intervals.